Analyst Forecast Bundling - Drake, Michael; Joos, Peter; Pacelli, Joseph; Twedt, Brady (Management Science, 2020)
Changing economic conditions over the past two decades have created incentives for sell-side analysts to both provide their institutional clients tiered services and to streamline their written research process. One manifestation of these changes is an increased likelihood of analysts’ issuing earnings forecasts for multiple firms on the same day. We identify this bundling property and show that bundling has increased steadily over time. We provide field evidence that the practice is a cost-saving measure, a natural by-product of analysts focusing on thematic research, and a reflection of forecast updating that occurs in advance of important events. Our empirical analyses show that bundled forecasts are less accurate, less bold, and less informative to investors than nonbundled forecasts. We also find that analysts who produce bundled forecasts provide valuable specialized services to their institutional clients. Our findings ultimately demonstrate that forecast bundling has important implications for the properties of analysts’ forecasts. This paper was accepted by Shiva Rajgopal, accounting.